Effect of wound irrigation on the prevention of surgical site infections: A meta‐analysis. Issue 7 (16th March 2022) - Fu, Chunmei; Meng, Linghong; Ma, Miguo; Li, Na; Zhang, Jingcen
Abstract: We performed a meta‐analysis to evaluate the effect of wound irrigation on the prevention of surgical site infections. A systematic literature search up to January 2022 was done and 24 studies included 4967 subjects under surgery at the start of the study; antibiotic irrigation was used with 1372 of them, 1261 were aqueous povidone‐iodine irrigation, and 2334 were saline irrigation or no irrigation for surgical site infections prevention in all surgical populations. We calculated the odds ratio (OR) with 95% confidence intervals (CIs) to evaluate the effect of different wound irrigation on the prevention of surgical site infections by the dichotomous method with a random or fixed‐influence model. Antibiotic irrigation had significantly lower surgical site infections in all surgical populations (OR, 0.48; 95% CI, 0.36‐0.62, P  < .001) compared with saline irrigation or no irrigation for the subject under surgery. Aqueous povidone‐iodine irrigation had significantly lower surgical site infections in all surgical populations (OR, 0.40; 95% CI, 0.20‐0.81, P  = .01) compared with saline irrigation or no irrigation for the subject under surgery. Antibiotic irrigation and aqueous povidone‐iodine irrigation significantly lowered surgical site infections in all surgical populations compared with saline irrigation or no irrigation for the subject under surgery. Further studies are required.